The Effectiveness of A Program Based on The Theory of Successful Intelligence in The Development of Creative Reading Skills of Sixth Grade Students - Al-Harbi, Hesa Juhaz Zaben (Journal of Educational and Psychological Sciences, 2021)
The current study aimed to identify the effectiveness of a program based on the theory of successful intelligence in developing creative reading skills among sixth grade students. To this end, the researcher has used the experimental approach with a quasi-experimental design for the two equivalent experimental and control groups. She has also used the following tools and materials; (1) a list of creative reading skills to be developed, (2) an achievement test to measure the creative reading skills, and (3) teacher's manual. The researcher has also validated the data collection tools and administered them on a random sample of the sixth-grade female students in the schools in Al-Rass governorate (N=60); 30 students for each group. Findings of the study revealed that there were statistically significant differences at the level of (0.05) between the experimental and control groups students' skills in the post -tests scores of creative reading skills for the benefit of the experimental group students who studied using the program based on the theory of the successful intelligence. The results also showed a significant positive impact of the program based on the theory of successful intelligence in developing the creative reading skills of the experimental group students. In light the previous findings, the researcher provided many recommendations and the most major ones were to take care of developing creative reading skills for different stages particularly the elementary stage, to use the program based on the theory of successful intelligence as it was found effective in developing the creative reading skills, and to hold training programs for Arabic language teachers and supervisors to orient them how to best employ the theory of successful intelligence in teaching and clarify its role in developing creative reading skills.
Keywords: A Program Based on the Theory of Successful Intelligence; the theory of successful intelligence; creative reading skills; Arabic language teaching